2016
DOI: 10.1007/s12272-016-0839-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol and its analogs on age-related macular degeneration in vitro

Abstract: Damage of retinal pigment epithelial (RPE) cells by A2E may be critical for age-related macular degeneration (AMD) management. Accumulation and photooxidation of A2E are known to be one of the critical causes in AMD. Here, we evaluated the protective effect of resveratrol (RES), piceatannol (PIC) and RES glycones on blue-light-induced RPE cell death caused by A2E photooxidation. A2E treatment followed by blue light exposure caused significant damages on human RPE cells (ARPE-19). But the damages were attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 61 publications
1
19
0
1
Order By: Relevance
“…и соавт. обнаружили, что ресвератрол и его аналоги защищают клетки сетчатки и вызванного HEV-излучением фото-повреждения [38]. В исследовании Richer и соавт.…”
Section: Sirt1unclassified
“…и соавт. обнаружили, что ресвератрол и его аналоги защищают клетки сетчатки и вызванного HEV-излучением фото-повреждения [38]. В исследовании Richer и соавт.…”
Section: Sirt1unclassified
“…Those studies provided increasing evidence that RESV has beneficial effects in neurodegenerative diseases such as AD [ 26 ], Parkinson’s Disease (PD) [ 27 ], and Amyotropic Lateral Sclerosis (ALS) [ 28 , 29 ]. Recently, protective effects of RESV have been investigated in vitro on retinal pigment epithelium cell death resulting from blue-light-induced damage [ 30 ], and in vivo on the rat model of diabetic retinopathy [ 31 ]. In this study, the effect of RESV in light-induced retinal damage of SAMP8 mice was analyzed to understand the mechanism of restoration of function of the affected retina following RESV administration in an aging animal model.…”
Section: Disscusionmentioning
confidence: 99%
“…In vitro and in vivo experiments have provided evidence about the biological effects of some natural plant polyphenols, therefore proposed as complement treatment in ocular diseases. In particular, resveratrol (RSV), a grape stilbenoid, revealed a modest beneficial impact on numerous cellular pathways implicated in age‐related ocular disorders, such as oxidative stress, inflammation, mitochondrial dysfunction, apoptosis and survival . Recent studies have demonstrated that RSV acts in a dose‐ and time‐dependent manner on MSCs, including human primary keratinocytes .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, resveratrol (RSV), a grape stilbenoid, revealed a modest beneficial impact on numerous cellular pathways implicated in age-related ocular disorders, such as oxidative stress, inflammation, mitochondrial dysfunction, apoptosis and survival. [24][25][26] Recent studies have demonstrated that RSV acts in a dose-and time-dependent manner on MSCs, including human primary keratinocytes. [27][28][29] In the last few years, our group has focused on the pluripotent and immune-modulator characteristics in f-LSCs defined by a proteomic profile especially enriched with remodelling and wound healing proteins, including pfn1 and integrin-1β.…”
Section: Introductionmentioning
confidence: 99%